Correlation among Self-Esteem, Writing Motivation, and Writing Achievement of the Fifth Semester Students of STKIP Muhammadiyah Kotabumi-Lampung Utara - Elis Susanti (ELTE Journal (English Languange Teaching and Education), 2015)
As writing belongs to one of the four English skills to be mastered by students and it is a very important component of communication, it is important to investigate the relationship of some affective aspects with students’ achievement in writing. Therefore, it is hopefully that English teachers or lecturers will be able to find the best solution for their students’ difficulties in learning writing. It was a correlational study consisting of three variables namely self-esteem (X1), writing motivation (X2), and writing achievement (Y). This study was going to investigate and answer four questions related to the correlation of the variables by administering questionnaires and a writing test to 50 out of 81 students of the fifth semester of STKIP Muhammadiyah Kotabumi-Lampung Utara. The questionnaires were used to collect the data of students’ self-esteem and writing motivation, while the writing test was conducted to measure the students’ writing achievement by asking the students to write a simple expository paragraph in accordance with the topics provided. The data analysis  resulted the H0 hypotheses were all rejected and Ha hypotheses were all accepted. To sum up, there is significant correlation among self-esteem, writing motivation and writing achievement of the fifth semester students of STKIP Muhammadiyah Kotabumi-Lampung Utara. Key Words: Self-Esteem, Writing Motivation, Writing Achievement